Formation of Banking in Western Transbaikalia in 19th Century: Merchant Initiatives - A. M. Plekhanova; A. А. Shirapov (Научный диалог)
An analysis of the contribution of regional merchants to the process of forming a system of credit and financial institutions in the territory of Western Transbaikalia is presented in the article. The history of both successful and unsuccessful attempts to create bank ing institutions in the region has been reconstructed on the basis of reporting and officework documentation stored in the funds of the State Archives of the Republic of Buryatia and the Irkutsk Region, the Russian State Historical Archive. It was found that the creation of the regional banking system was based not on the state, but on the private initiative; the key role in the process  was  played  by the merchants. According to the authors, in the process of organizing banks and loan offices, representatives of the merchants were guided not only by making a profit, but envisaged the use of part of the proceeds for charitable purposes. It was revealed that merchant initiatives were caused not only by the desire to expand the opportunities for entrepreneurial activity, but also by the desire to contribute to the development of the native land. It is concluded that the Transbaikal merchants played an important role in the socio-economic development of Western Transbaikalia and became the main driving force in integrating the region’s economy into the all-Russian financial system.